Design and implementation of a management system of academic quality management in the United Graduate Faculty of Engineering of the UNMSM - Inche Mitma, Jorge (2010)
The industrial faculty posgrade unit of UNMSM (UPG) since 2007 had an accelerated growing in programs and students, in this scenario, the academic - management system was not enough to the higher education modern approach, generating the next question: What kind of quality management design is appropriate and how to must be implemented at the UPG taking as a base the ISO 9001 standard?. In order to answer this question, the work team applied concepts like continuously improvement and the process map analysis ; having as a result the validation of the System Management of Academic – Administrative Quality in two academic semesters.